Modeling future habitats to identify suitable sites for ex situ conservation of the endangered palm Metroxylon vitiense (H. Wendl.) H. Wendl. ex Benth. & Hook. f. in Fiji - Itaya, Akemi; Miyamori, Masamitsu; Ehara, Hiroshi; Naito, Hitoshi; Rounds, Isaac; Naikatini, Alivereti; Tuiwawa, Marika (Tropical ecology, 2022)
Climate change and human-centered development have endangered the survival of many species. The purpose of this study was to investigate, using MaxEnt, changes in the habitat suitable for the endangered palm Metroxylon vitiense (H. Wendl.) H. Wendl. ex Benth. & Hook. f. in Fiji resulting from a changed climate. MaxEnt is a maximum entropy-based machine learning program, and it can estimate the probability distribution for the occurrence of a species based on environmental constraints. The results indicated that precipitation in the driest month had the highest gain when it was considered in isolation, indicating that this factor is the most important environmental variable influencing the distribution of this palm. Moreover, precipitation in the driest quarter and annual precipitation may influence to some extent the distribution of the species. Predictions indicated that future suitable habitats for M. vitiense may occur not only in the coastal area, but also away from it. Although this prediction has associated uncertainty, the suitable area may increase to 409.7% and 240.9% of the area of current suitable habitats. The coastal area, where the current habitat it located, is subject to rapid development and may be affected by sea-level rise. In this case, ex situ conservation would be effective. In order to avoid risk, this study suggests that it would be appropriate to plant M. vitiense away from coastal areas. However, ensuring there is sufficient area for transplantation is a major issue.